2013
DOI: 10.1089/ten.tea.2012.0376
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Microporous Chitosan Hydrogel/Nanofibrin Composite Bandage for Skin Tissue Regeneration

Abstract: In this work, we have developed chitosan hydrogel/nanofibrin composite bandages (CFBs) and characterized using Fourier transform-infrared spectroscopy and scanning electron microscopy. The homogeneous distribution of nanofibrin in the prepared chitosan hydrogel matrix was confirmed by phosphotungstic acid-hematoxylin staining. The mechanical strength, swelling, biodegradation, porosity, whole-blood clotting, and platelet activation studies were carried out. In addition, the cell viability, cell attachment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…In the in vitro analysis of these nanoparticles, an increase in calcium absorption of the fibroblasts and an increase in the proliferation rate of fibroblasts was observed (26) . Finally, the results of study A12, performed using chitosan hydrogel mixed fibrin nanoparticles (CFBs), through in vivo and in vitro tests, reinforced the evidence of the contribution of the use of nanoparticle-based products to accelerate the process of blood coagulation, promotion of platelet activation and wound healing (27) . The advantage of using fibrin in nanoformulation is due to the ideal biomimetic matrix, in which the active portions of fibrin are ready for platelet activation, thus inducing a rapid healing process (27) .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the in vitro analysis of these nanoparticles, an increase in calcium absorption of the fibroblasts and an increase in the proliferation rate of fibroblasts was observed (26) . Finally, the results of study A12, performed using chitosan hydrogel mixed fibrin nanoparticles (CFBs), through in vivo and in vitro tests, reinforced the evidence of the contribution of the use of nanoparticle-based products to accelerate the process of blood coagulation, promotion of platelet activation and wound healing (27) . The advantage of using fibrin in nanoformulation is due to the ideal biomimetic matrix, in which the active portions of fibrin are ready for platelet activation, thus inducing a rapid healing process (27) .…”
Section: Discussionmentioning
confidence: 87%
“…Finally, the results of study A12, performed using chitosan hydrogel mixed fibrin nanoparticles (CFBs), through in vivo and in vitro tests, reinforced the evidence of the contribution of the use of nanoparticle-based products to accelerate the process of blood coagulation, promotion of platelet activation and wound healing (27) . The advantage of using fibrin in nanoformulation is due to the ideal biomimetic matrix, in which the active portions of fibrin are ready for platelet activation, thus inducing a rapid healing process (27) . At the end of this discussion, the results of the studies suggest evidence that nanoparticle-based dressings are effective and beneficial.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In vivo studies on Sprague-Dawley rats using this hydrogel have shown faster wound healing response evidenced by increased collagen deposition. 51 Hydrogels are also effective in the controlled release of impregnated drugs, which is essential for the sustained stimulation of tissue growth. An interesting study by Jaiswal et al has shown that poly(vinyl alcohol) hydrogel impregnated with epigallocatechin gallate is very effective in healing wounds by improving angiogenesis, restoring epithelialization, and decreasing the inflammatory response.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Then, cells were washed and suspended in PBS containing 0.1% glucose, 0.5 mM EDTA and 5 mM 2 0 ,7 0 -dichlorodihydrofluorescein diacetate (H 2 DCF-DA) (Sudheesh Kumar et al, 2013). Fluorescence light was monitored in a Tecan Infinite 1 M200 absorbance mode microplate reader at 495 nm (measurement wavelength) and at 525 nm (reference wavelength) (Mytych et al, , 2015b.…”
Section: Oxidative Stressmentioning
confidence: 99%